Enhanced optical properties of high-density (> 10(11)/cm(2)) InAs/AlAs quantum dots by hydrogen passivation - Park, SK; Tatebayashi, J; Nakaoka, T; Sato, T; Park, YJ; Arakawa, Y (JAPAN SOC APPLIED PHYSICS, 2004)
We have achieved a large increase (by a factor of up to 3200) in photoluminescence emission from InAs/AlAs quantum dot structures using the GaAs insertion layer and by hydrogen passivation at room temperature. The hydrogen passivation can lead to the reduction in a number of nonradiative recombination centers, and thus can increase the photoluminescence efficiency. After the treatments, the linewidth and the peak position of the luminescence were negligibly changed, indicating that the samples were not damaged during the plasma treatments. In time-resolved photoluminescence measurements, the decay time of hydrogenated samples was about twice as long as those of as-grown samples due to the passivated defects in surrounding barrier materials.
Keywords: TEMPERATURE-DEPENDENCE; GAAS